What price economic growth? - Baumol, William J.; Knorr, Klaus (Englewood Cliffs, N.J. : Prentice-Hall, 1961)
This book is on the demand for faster economic growth and it's significance.
Includes bibliographical footnotes.
oo 07/11/2018
Loans
Keywords: Economic development; United States